Pearl Harbor, 1941 - McClister, Caitlin (The Toro Historical Review, 2022)
The Japanese attack on Pearl Harbor is one of the most memorable moments in United States history. As time has passed, new evidence has been discovered by scholars that presents a few interesting themes. One is that the bombing was not a complete surprise, meaning that there were multiple individuals who had some awareness of the possibility of an attack. The second is that the damage experienced by the United States was not quite as devastating as previously thought. Through this essay, I hope to answer these questions and provide insight on some of the new information that has emerged over the years since 1941.